VIVOICE: An Effort to Promote EFL Learners’ Self-Regulated Learning during the COVID-19 Outbreak - Bimma Dwy Fajar Mukti; Yudi Basuki (Universitas PGRI Madiun, 2020)
COVID-19 is a new pandemic affecting every sector worldwide including in educational environment. Thus, a mixture of various e-learning is required in order to make TLP possible. Besides, having self-regulated learning is beneficial for each student to survive during study from home because of the pandemic. Thus, most students need a media and teaching instruction that motivate them better than the existed media. In this way, this research is aimed at developing VIVOICE (Virtual Vocabulary Voice) to promote EFL learners’ self-regulated vocabulary learning. The research design is R&D completed with quasi-experimental research design to prove the effectiveness of the developed product. A set of questionnaire and interview are used to collect the data of the research. The finding of need analysis showed that most students need a better media of TLP during the outbreak. However, the product was developed based on the result of the students’ need analysis, Buku Ajar Vocabulary 1 (@televocabot) (@televocabot), evaluation and suggestion from the expert validators. More importantly, the findings of the field testing showed that product gets supportive support from the students and proved practical enough during the outbreak. The quasi-experimental in field testing done to prove the effectiveness of the developed product resulted the mean score of experimental groups is increased from 75.9 to 80.8 while control group is also increased 76.1 to 76.7. Then, after the analysis by using SPSS version 25, the value of Sig. (2-tailed) in independent sample t-test was 0.035 (<0.05) meaning that there is a significance difference between experimental group and control group. Meanwhile from paired sample t-test result, the value of Sig. (2-tailed) was 0.005 (<0.05) that mean there is an improvement of self-regulated learning level in the experimental group after using VIVOICE during the outbreak. In conclusion, VIVOICE (Virtual Vocabulary Voice) is an effective audio-visual application to promote EFL learners’ self-regulated learning during the outbreak.